EFFECTIVE DA'WAH STRATEGIES IN INDONESIA'S DIVERSE SOCIETY: INSIGHTS FROM USTADZ ABDUL SOMAD AND BUYA RAMZI WITHIN THE SCOPE OF ISLAMIC EDUCATION - Satra, Alihan; Wulandari, Siska; Antika, Rindi; Mukaromah, Indah; Nurkholiza, Hafizah (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study explores effective dakwah strategies employed by Ustadz Abdul Somad and Buya Ramzi in Indonesia’s pluralistic and multicultural society, with a focus on their implications for Islamic education. Using a qualitative content analysis approach, the research examines how both figures adapt their preaching styles to address diverse cultural, social, and religious contexts. Ustadz Abdul Somad utilizes a direct, educational, and humorous approach that resonates with various social groups, while Buya Ramzi incorporates local cultural values, arts, and popular media to deliver Islamic messages in a persuasive and peaceful manner. The findings highlight that inclusive, adaptive, and communicative strategies are essential in conveying Islamic teachings effectively. Moreover, these dakwah approaches provide valuable insights for Islamic education by emphasizing relevance, tolerance, and social harmony in shaping students who can thrive in Indonesia’s diverse society. This study contributes to advancing the understanding of contextualized dakwah practices that align with contemporary educational and social challenges. Penelitian ini mengkaji strategi dakwah efektif yang digunakan oleh Ustadz Abdul Somad dan Buya Ramzi dalam masyarakat Indonesia yang pluralistik dan multikultural, dengan fokus pada implikasinya terhadap pendidikan Islam. Dengan pendekatan analisis isi kualitatif, penelitian ini meneliti bagaimana kedua tokoh tersebut menyesuaikan gaya dakwahnya untuk menjangkau konteks budaya, sosial, dan keagamaan yang beragam. Ustadz Abdul Somad menggunakan pendekatan dakwah yang lugas, edukatif, dan penuh humor yang diterima oleh berbagai kelompok sosial, sedangkan Buya Ramzi mengintegrasikan nilai-nilai budaya lokal, seni, dan media populer dalam menyampaikan pesan Islam secara persuasif dan damai. Temuan menunjukkan bahwa strategi dakwah yang inklusif, adaptif, dan komunikatif sangat penting dalam menyampaikan ajaran Islam secara efektif. Selain itu, pendekatan dakwah tersebut memberikan wawasan berharga bagi pendidikan Islam dengan menekankan relevansi, toleransi, dan harmoni sosial dalam membentuk peserta didik yang mampu hidup harmonis di tengah keberagaman masyarakat Indonesia. Penelitian ini berkontribusi dalam memperluas pemahaman tentang praktik dakwah kontekstual yang selaras dengan tantangan pendidikan dan sosial kontemporer.